Fetal treatment of sacrococcygeal teratoma: state of the art - M. C. Cianci; M. C. Cianci; G. Fusi; F. Morini; F. Morini; E. Severi; A. Morabito; A. Morabito; C. Grimaldi (Frontiers in Pediatrics)
Antenatally detected sacrococcygeal teratoma (SCT) is a potentially life-threatening condition. Its prenatal management remains a topic of debate due to its association with fetal and maternal complications. This review delves into various fetal approaches to SCT, elucidating the roles of different procedures. Overall, fetal treatments are proposed to highly selected patients, with severe complications of SCT who carry a dismal prognosis and a high-risk in utero death. No shared protocols for patient and/or procedure selection exist thus overall management of these patients is highly dependent on the team skills and facility resources. Despite the general feeling that a prenatal diagnosis of SCT involves a high mortality risk, this comprehensive review demonstrates that advancements in fetal SCT treatment positively affect both fetal and maternal outcomes.